Temperature Insensitive Vector Bending Sensor Based on Asymmetrical Cascading SMF-PCF-SMF Structure - Guangwei Fu; Yunpu Li; Qifeng Li; Jiandong Yang; Xinghu Fu; Weihong Bi (IEEE Photonics Journal)
A temperature insensitive vector curvature sensor of photonic crystal fiber (PCF) is presented based on core-offset splicing and waist-enlarged fiber taper. Obvious red and blue shifts in transmission spectrum appear at two symmetrical bending directions with sensor length of 10, 13, 16, and 19 mm and vector curvature of 0.12–1.06 m–1. The longer the sensor length is, the larger the curvature sensitivity is. The corresponding sensitivity with concave bending and convex bending are increased on average by 0.44 and 0.43 nm/m–1, respectively, while the sensor length increases per 1 mm. Moreover, when sensor length is 16 mm, the temperature sensitivity is only 1.73 pm/°C in 20–90 °C; therefore, it has the temperature insensitive property. Obviously, the reported sensor could avert cross-sensitivity of temperature and curvature when measured together. It is prospective being used in industrial production, building monitoring, aerospace, and other fields in view of its easy fabrication, simple structure, and high sensitivity.